Culture and Learner Beliefs: A Study of Three Malay Postgraduate Students - Faizah A Majid (UiTM Publisher, 2008)
Culture influences how people experience. Although there is literature on how culture can influence adult learners' orientation to learning, there is little on how culture influences the nature of successful learning amongst adults (Merriam and Mohamad, 2000). The purpose of this paper is to examine how cultural values influence a selected group of successful adult learners' views on learning in the Malaysian education context. A qualitative research design was adopted to explore this question. Three postgraduates who had completed their studies on time were interviewed. Using the constant comparative method of data analysis (Wellington, 2000), five cultural values as identified by Abdullah (1996) and Hofstede (1991); collectivistic, religious, relationship-oriented, hierarchical, and face conscious were used to serve as the main themes in the analysis. In analysing the data, three cultural values emerged; religious, relationship-oriented and, collectivistic. These findings have implications for understanding how cultural values may influence adult Malay students' views on learning.